Flow lines analysis - Mohd Azri, Jaludin (Universiti Malaysia Sarawak (UNIMAS), 2009)
Flow nets are a graphical analysis method that can be used to seepage flow path to determine the rate of seepage flow, the magnitude of seepage pressure and predict the possibility of instability of the soil for example where the water seeps through the embankment and comes to the surface at the downstream side of an earth dam. A flow net is constructed from a set of now lines and a set angles to each other thai will foml a flow channel. A study of flow nel was conduc ted by sand modeling method using CUSSONS P6520 penneability "pparalUs. Seveml types of seepage comra] observed to differentiate the effect of each type of drainage on the flow of water through embankment.